2019
DOI: 10.9734/jcti/2018/v8i230093
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma – Lessons Learned about Patterns of Care and Contributory Factors from 5 Years’ Experience in a Tertiary Care Center in Eastern India

Abstract: Objectives: Retinoblastoma is the most common intraocular malignancy afflicting children worldwide. Even though there are enough data about the epidemiology of retinoblastoma in western population, there are only few reports from developing countries like India. In this retrospective study, we aimed to describe the epidemiological patterns, survival characteristics and prognostic factors of retinoblastoma. Materials and Methods: From medical records, we retrospectively analyzed the data of 68 children di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 4 publications
(4 reference statements)
3
8
0
Order By: Relevance
“…24 Other studies have shown an association, although it was not significant between the lag time to diagnosis and death, which had a lower cut-off, in 3 months (p = .96), 5 months with HR 7.7 (.129-46.13), and 6 months (95% CI: OR .71-1.51). 15 The lag time to therapy in this study has a median value of 1 month (0-7.75). This is consistent with a previous study in India that showed the lag time to therapy interval ranged from days to 12 months, with a median value of 1 month.…”
Section: Duration Of Treatment (Months)mentioning
confidence: 75%
See 4 more Smart Citations
“…24 Other studies have shown an association, although it was not significant between the lag time to diagnosis and death, which had a lower cut-off, in 3 months (p = .96), 5 months with HR 7.7 (.129-46.13), and 6 months (95% CI: OR .71-1.51). 15 The lag time to therapy in this study has a median value of 1 month (0-7.75). This is consistent with a previous study in India that showed the lag time to therapy interval ranged from days to 12 months, with a median value of 1 month.…”
Section: Duration Of Treatment (Months)mentioning
confidence: 75%
“…In a study in India, the onset was 22 ± 19.7 months. 15 Research in Brazil showed a median of 18 months (1-58 months). 17 The onset varied depending on the dominance of the study subjects having hereditary or nonhereditary retinoblastoma.…”
Section: F I G U R E 1 Overall Survival Analysismentioning
confidence: 99%
See 3 more Smart Citations